Urban Sustainability in the US Cities Take Action - Keeley, Melissa; Benton-Short, Lisa.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
Cities are stepping forward to address the critical sustainability challenges of the 21st century. Meeting the demands of complex issues requires municipalities to evaluate problems and their solutions in more holistic, integrated, and collaborative ways. Drawn from plans and progress reports from more than fifty US cities, this book examines how urban leaders conceptualize sustainability, plan effective strategies, and take action. Chapters examine various topical themes including equity, the green economy, climate change, energy, transportation, water, green space, and waste. Throughout the text, the authors highlight best practices in innovative solutions, recognizing the multiple benefits of sustainability projects, environmental justice, governance, education and communication. .
1. Conceptualizing Sustainability -- 2. The Planning Process -- 3. Climate Adaptation -- 4. Transportation -- 5. Energy -- 6. Green Space -- 7. Water -- 8. Waste and Recycling -- 9. Economy and Green Jobs -- 10. Equity and Environmental Justice -- 11. Conclusion and Challenges to Sustainability Implementation.
Keywords: Sociology, Urban; Urban Sociology